Pengaruh Soft Skills terhadap Kesiapan Kerja melalui Pengalaman Magang sebagai Variabel Intervening pada Mahasiswa Prodi Manajemen Angkatan 2021 Universitas Jambi - Nuri Dayanti; Sry Rosita; Hendriyaldi Hendriyaldi (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of soft skills on job readiness through internship experience as an intervening variable in Management Study Program students, batch 2021, Jambi University. This study uses a quantitative method with data collection techniques by distributing questionnaires to 142 respondents from various academic and professional backgrounds. Hypothesis testing utilizes descriptive analysis techniques with the support of SmartPLS software to examine the relationships between the identified variables. The findings of this study indicate that: (1) soft skills have a positive and significant influence on job readiness, (2) soft skills have a positive and significant influence on internship experience, (3) internship experience has a positive and significant influence on job readiness, (4) soft skills have a positive and significant influence on job readiness through internship experience as an intervening variable in Management Study Program students, batch 2021, Jambi University. These results emphasize the vital role of soft skills and internship experience in improving job preparedness.